Impact of organ shape variations on margin concepts for cervix cancer ART. Issue 3 (September 2016) - Seppenwoolde, Yvette; Stock, Markus; Buschmann, Martin; Georg, Dietmar; Bauer-Novotny, Kwei-Yuang; Pötter, Richard; Georg, Petra
Abstract: Background and purpose: Target and organ movement motivate adaptive radiotherapy for cervix cancer patients. We investigated the dosimetric impact of margin concepts with different levels of complexity on both organ at risk (OAR) sparing and PTV coverage. Material and methods: Weekly CT and daily CBCT scans were delineated for 10 patients. The dosimetric impact of organ shape variations were evaluated for four (isotropic) margin concepts: two static PTVs (PTV6mm and PTV15mm ), a PTV based on ITV of the planning CT and CBCTs of the first treatment week (PTVART ITV ) and an adaptive PTV based on a library approach (PTVART Library ). Results: Using static concepts, OAR doses increased with large margins, while smaller margins compromised target coverage. ART PTVs resulted in comparable target coverage and better sparing of bladder (V40 Gy: 15% and 7% less), rectum (V40 Gy: 18 and 6 cc less) and bowel (V40 Gy: 106 and 15 cc less) compared to PTV15mm . Target coverage evaluation showed that for elective fields a static 5 mm margin sufficed. Conclusion: PTVART Library achieved the best dosimetric results. However when weighing clinical benefit against workload, ITV margins based on repetitive movement evaluation during the first week also provide improvements over static margin concepts.